Economic consequences of noncompliant behavior of patients with chronic renal failure and ways of its correction - Yu. S. Lysenko; O. Yu. Mikita; A. V. Pinchuk; M. Sh. Khubutiya (Трансплантология (Москва), 2022)
Introduction. Kidney transplantation is the main high-tech type of medical care aimed at saving the life of a patient with chronic kidney disease in the terminal stage of the disease. The amount of economic costs for the treatment of patients with chronic renal failure depends on the results of transplantation: the calculation for 1 patient with a favorable outcome is 1,665,110.19 rubles, with an unfavorable outcome – 2,932,078.07 rubles. Noncompliant behavior (non-compliance with doctors' recommendations) directly affects the effectiveness and outcome of transplantation, as well as its economic component. In order to minimize the factors affecting transplant rejection after surgery due to patient noncompliant behavior, it is necessary to assess adherence to treatment at the stages before and after transplantation.Aim. To assess the adherence to treatment of patients with chronic renal failure of the N.V. Sklifosovsky Research Institute for Emergency Medicine at all stages of kidney transplantation in order to identify risk groups for noncompliant behavior.Material and methods. The study was conducted on the basis of the Department of Kidney and Pancreas Transplantation of the N.V. Sklifosovsky Research Institute for Emergency Medicine. 3 groups of patients with a diagnosis of "Chronic renal failure" were examined: 1. 48 patients before kidney transplantation who were on the waiting list. The average age of patients: 48.06±10.21 years. Gender composition of the group: 40% men, 60% women. 2. 62 patients a month after kidney transplantation. The average age of patients: 49.49±11.04 years. Gender composition of the group: 41% men, 59% women. 3. 22 patients more than 1 month after kidney transplantation. The average age of patients: 43.39±12.29 years. Gender composition of the group: 41% men, 59% women.The assessment of the level of adherence to treatment was carried out using the following psychodiagnostic techniques: "Quantitative assessment of adherence to treatment", "Social significance of the disease" and "Compliance level".Results. The data obtained by us demonstrate the highest level of adherence to treatment in the waiting list group (90.67±18.91 points), in the group a month after transplantation this level decreases (71.29±22.70 points), the lowest indicators (65.73±23.47 points) in the group a few months after kidney transplantation.Conclusion. Noncompliant behavior of patients can affect the treatment outcomes. According to our study, patients on the waiting list have the highest rates in terms of adherence to treatment, the group of patients a month after transplantation is characterized by a decrease in all indicators, and the group a few months after kidney transplantation is characterized by the lowest parameters. According to the dynamics of changes in the level of adherence to treatment in the groups we examined, it is recommended to prevent noncompliant behavior in order to increase the treatment effectiveness and minimize financial costs for the consequences of transplant rejection due to the patient's fault.